Primer-induced labeling of pea and field bean chromosomes in situ and in suspension - Macas, J; Dolezel, J; Gualberti, G; Pich, U; Schubert, I; Lucretti, S (BioTechniques, 1995)
A protocol for primed in situ DNA labeling (PRINS) was optimized for pea (Pisum sativum L.) and field bean (Vicia faba L.) chromosomes attached to coverslips. Cloned DNA or synthetic oligonucleotides were used as probes for repetitive DNA sequences (rDNA, Fok-element) and different reaction conditions were tested to achieve the highest specific signal-to-background ratio. A procedure based on direct labeling by fluorescein-dUTP was compared with an indirect one using digoxigenin detected by fluorescently labeled antibody. Under optimal conditions, strong and specific signals were obtained exclusively on chromosome regions known to contain respective DNA sequences. Compared to the direct labeling, significantly stronger signals were obtained when the indirect procedure was used. Both types of labeling were successfully applied to chromosomes in suspension and were shown to produce signals comparable to that obtained with chromosomes attached to coverslips. It is expected that primed in situ DNA labeling en suspension (PRINSES) will provide a basis for flow-cytometric discrimination and sorting of otherwise indistinguishable chromosomes according to their specific fluorescent labeling.
Keywords: hybridizace in situ; sekvence nukleotidů; DNA Probes; polymerázová řetězová reakce; Plants, Medicinal; fluorescenční mikroskopie; Repetitive Sequences, Nucleic Acid; molekulární sekvence - údaje; In Situ Hybridization; Nucleolus Organizer Region; DNA Primers; fluorescein; Fabaceae; DNA rostlinná; DNA, Plant; fluoresceiny; Microscopy, Fluorescence; organizátor jadérka; deoxyuracilnukleotidy; DNA primery; Fluoresceins; DNA sondy; repetitivní sekvence nukleových kyselin; Molecular Sequence Data; Polymerase Chain Reaction; Base Sequence; Fluorescein; Deoxyuracil Nucleotides; léčivé rostliny